2015
DOI: 10.1002/rcs.1659
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid position/force control of an active handheld micromanipulator for membrane peeling

Abstract: Background Peeling procedures in retinal surgery require micron-scale manipulation and control of sub-tactile forces. Methods Hybrid position/force control of an actuated handheld microsurgical instrument is presented as a means for simultaneously improving positioning accuracy and reducing forces to prevent avoidable trauma to tissue. The system response was evaluated, and membrane-peeling trials were performed by four test subjects in both artificial and animal models. Results Maximum force was reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Experiments on bandages and raw chicken eggs have revealed that controlled micro-vibrations provide ease in delaminating membranes. Automatic force-limiting control has also been demonstrated with the 6-DoF Micron system for membrane peeling using a parallel force/position control system [202].…”
Section: Closed-loop Control For Handheld Systemsmentioning
confidence: 99%
“…Experiments on bandages and raw chicken eggs have revealed that controlled micro-vibrations provide ease in delaminating membranes. Automatic force-limiting control has also been demonstrated with the 6-DoF Micron system for membrane peeling using a parallel force/position control system [202].…”
Section: Closed-loop Control For Handheld Systemsmentioning
confidence: 99%
“…The single-leader-single-follower topology (SL/SF, see Figure 4) has been used, as mentioned before, to augment human sensorimotor competence [28,86]. A successful example of an SL/SF telerobotic system is the da Vinci Surgical System [23], using which it is now possible to conduct minimally invasive laparoscopic surgeries inside a patient's body with an ultra-precision, reliability, and safety [65,87,88]. This topology transfers the pose commands of the surgeon collected by the leader console to the follower robot inserted through small incisions inside the patient body to conduct the surgery under the direct control of the surgeon while augmenting the sensory and motor skills of the surgeons [65,[87][88][89][90], as explained in the next subsections.…”
Section: Single-leader Single-follower Topology (Sl/sf)mentioning
confidence: 99%
“…It must be noted however, that providing direct force feedback is not the only approach taken by researchers for reducing applied force in retinal membrane peeling. In [140] for example, an active handheld micromanipulator [141] is implemented under a hybrid position/force control schema that is shown to reduce the maximum force by more than 50% in experiments on both artificial and animal models. Table III, summarizes the research studies that have investigated the effects of haptic feedback in robot-assisted surgery.…”
Section: E Microsurgical Tasksmentioning
confidence: 99%